Instant Netcat starter : learn to harness the power and versatility of Netcat, and understand why it remains an integral part of IT and security toolkits to this day /: learn to harness the power and versatility of Netcat, and understand why it remains an integral part of IT and security toolkits to this day. (2013) - Yerrid, K. C
No abstract available